Effects of (de)motivating supervision styles on junior doctors’ intrinsic motivation through basic psychological need frustration and satisfaction: an experimental vignette study - van der Goot, Wieke E.; Van Yperen, Nico W.; Albers, Casper J.; Jaarsma, A. Debbie C.; Duvivier, Robbert J. (Advances in health sciences education : theory and practice, 2025)
In clinical practice, junior doctors regularly receive supervision from consultants. Drawing on Basic Psychological Needs Theory, consultants’ supervision styles are likely to affect junior doctors’ intrinsic motivation differently in terms of psychological need frustration and psychological need satisfaction. To examine the effects of (de)motivating supervision styles, we conducted two experimental vignette studies among junior doctors. In Study 1 ( N = 150, 73.3% female), we used a 2 (need support: high vs. low ) x 2 (directiveness: high vs. low ) between -subjects design and, in Study 2, a within -subjects design with the same factors ( N = 46, 71.7% female). Both studies revealed a consistent positive effect of need-supportive supervision styles on psychological need satisfaction (+), need frustration (-), and intrinsic motivation (+). Particularly in Study 2, the main effect of need-supportive styles was strengthened by supervisor’s directiveness. Moreover, in both studies, the effects of supervision styles on intrinsic motivation were explained through psychological need frustration and psychological need satisfaction. We discuss the implications of these findings for postgraduate clinical training.